(untitled) (Journal of Dhaka National Medical College & Hospital, 2018)
Background: Erythrocyte G-6PD enzyme deficiency is an important cause of Hemolytic anemia with consequent increase in Reticulocyte count and decrease in MCH. Objectives: To assess the Reticulocyte count and MCH in Erythrocyte G-6PD enzyme deficient with hemolytic anemia in order to find their status. Methods: The cross sectional study was carried out in the Department of physiology, BSMMU, Dhaka from July 2002 to 2003 to observe the RC (Reticulocyte count) and MCH in patient with hemolytic anemia. For this, total number of 50 hemolytic anemic patients (Groups-B) with age ranged from 5 to 30 years of both sexes was studied. Among them, 25 were without G-6PD deficient hemolytic anemia (B1) and 25 were hemolytic anemia with G-6PD deficiency(group-B2).Age and sex matched 30 apparently healthy subjects with normal blood G-6PD were included to observe baseline data (Group-A)and also for comparison. All the subject were selected from out Patient Department of Hematology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka. Blood erythrocyteG-6PD enzyme level,Reticulocyte count and MCH were measured by standard laboratory techniques. Analysis of data was done by unpaired Student’t’ test. Results: Reticulocyte count was significantly higher Group B2 vs. Group A and also Group B1 which was statically significant. MCH was significantly lower Group B2 vs. Group A and also Group B1 which was statically significant. Conclusion: From this study, it may be concluded that, increased hemolysis of RBC with high Reticulocyte count and low MCH occur in G-6PD deficient hemolytic anemic patients which may be membrane defect. J. Dhaka National Med. Coll. Hos. 2018; 24 (01): 18-22